2018
DOI: 10.4251/wjgo.v10.i10.317
|View full text |Cite
|
Sign up to set email alerts
|

Histo-molecular oncogenesis of pancreatic cancer: From precancerous lesions to invasive ductal adenocarcinoma

Abstract: Pancreatic cancer is a lethal malignancy, whose precursor lesions are pancreatic intraepithelial neoplasm, intraductal papillary mucinous neoplasm, intraductal tubulopapillary neoplasm, and mucinous cystic neoplasm. To better understand the biology of pancreatic cancer, it is fundamental to know its precursors and to study the mechanisms of carcinogenesis. Each of these precursors displays peculiar histological features, as well as specific molecular alterations. Starting from such pre-invasive lesions, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 70 publications
2
36
0
4
Order By: Relevance
“…Our data clearly indicated that CD117 was expressed more frequently and with more diffuse/stronger staining patterns in IOPNs compared to the other IPMN subtypes [1][2][3]. This marker had been already described to be expressed in neoplasms composed of cells rich in mitochondria [1,[24][25][26], and our findings confirmed this kind of association.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our data clearly indicated that CD117 was expressed more frequently and with more diffuse/stronger staining patterns in IOPNs compared to the other IPMN subtypes [1][2][3]. This marker had been already described to be expressed in neoplasms composed of cells rich in mitochondria [1,[24][25][26], and our findings confirmed this kind of association.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, IOPN diagnosis is performed with histological evaluation, but it should be further confirmed by immunohistochemistry for a definitive classification [1,2]. This is based on the presence of positive staining patterns for markers such as MUC5AC, which is usually positive in all IPMN subtypes and is helpful in rule out an intraductal tubulopapillary neoplasm (typically MUC5AC negative); MUC6, for the differential diagnosis with the other IPMN subtypes (usually MUC6 negative in particular gastric and intestinal subtypes); and Hep Par-1, a cytoplasmic marker which is also positive in hepatocellular carcinoma and other cancer types composed of cells rich in mitochondria [1,2]. Table 1 summarizes the different staining patterns of mucins in the whole spectrum of intraductal lesions of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITPN is considered a precursor lesion to invasive pancreatic ductal adenocarcinoma [ 4 , 11 , 21 23 ]. Approximately 40% to 50% of ITPN cases harbor an invasive component and they should be referred to as cases of “ITPN with an associated invasive carcinoma” [ 2 , 7 , 10 , 22 ]. Male sex, large tumor size, dilated pancreatic duct with pancreatoliths and high Ki-67 labelling index could be considered as predictive factors for invasiveness [ 2 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…More in detail, PanINs are non-infiltrating microscopic intraductal lesions with diameter <0.5 cm, composed of cuboid/columnar mucinous cells with varying degree of dysplasia, from low-grade (PanIN 1) to high-grade (PanIN 3), the latter one almost exclusively reported in association with infiltrating PDAC [26]. Early lesions (PanINs 1) show frequent KRAS somatic mutations, while PanINs 3 display also CDKN2A, TP53, and SMAD4 mutations, all of which significantly enriched in fully transformed PDAC (see below), as TP53 and SMAD4 inactivation appear to be the latest events of the molecular cascade that lead to overt PDAC.…”
Section: Pancreatic Ductal Adenocarcinoma: From Histology To Early Gementioning
confidence: 99%